2008
DOI: 10.1038/jcbfm.2008.32
|View full text |Cite
|
Sign up to set email alerts
|

Neural Progenitor Cells Treated with EPO Induce Angiogenesis through the Production of Vegf

Abstract: Recombinant human erythropoietin (rhEPO) induces neurogenesis and angiogenesis. Using a coculture system of mouse brain endothelial cells (MBECs) and neural progenitor cells derived from the subventricular zone of adult mouse, we investigated the hypothesis that neural progenitor cells treated with rhEPO promote angiogenesis. Treatment of neural progenitor cells with rhEPO significantly increased their expression and secretion of vascular endothelial growth factor (VEGF) and activated phosphatidylinositol 3-ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 37 publications
2
84
0
1
Order By: Relevance
“…A recent report BLOOD, 28 JANUARY 2010 ⅐ VOLUME 115, NUMBER 4 For personal use only. on May 12, 2018. by guest www.bloodjournal.org From demonstrated that EPO-induced angiogenesis was via the induction of VEGF in neural progenitor cells 27 ; however, we found that an anti-VEGF antibody added to the human CD34 ϩ EPCs had minimal effect on NO induction ( Figure 3B), even though the concentration of anti-VEGF antibody was able to block stimulation of NO of exogenously added VEGF (data not shown). Thus, EPO stimulation of NO was strictly dependent on the VEGF-R2 receptor.…”
Section: Resultsmentioning
confidence: 49%
“…A recent report BLOOD, 28 JANUARY 2010 ⅐ VOLUME 115, NUMBER 4 For personal use only. on May 12, 2018. by guest www.bloodjournal.org From demonstrated that EPO-induced angiogenesis was via the induction of VEGF in neural progenitor cells 27 ; however, we found that an anti-VEGF antibody added to the human CD34 ϩ EPCs had minimal effect on NO induction ( Figure 3B), even though the concentration of anti-VEGF antibody was able to block stimulation of NO of exogenously added VEGF (data not shown). Thus, EPO stimulation of NO was strictly dependent on the VEGF-R2 receptor.…”
Section: Resultsmentioning
confidence: 49%
“…Indeed, examination of trophic factor levels in the media of OGD-exposed cultured menstrual blood-derived stem cells reveals the up-regulation of VEGF, BDNF, NT-3, but not GDNF. Recent reports have implicated this set of trophic factors as mediating therapeutic benefi ts of transplanted stem cells in a variety of CNS disorders, including stroke [42][43][44][45][46][47]. In view of clinical product development, there may be less safety and toxicity concerns for peptide delivery compared to cell therapy.…”
Section: Figmentioning
confidence: 99%
“…41 Epo exhibits antiapoptotic and antiinflammatory effects acutely after neonatal brain injury [42][43][44][45][46] and promotes neurogenesis, plasticity, and tissue remodeling after hypoxia-ischemia. 15,[47][48][49][50] In animal models of neonatal stroke, Epo increases proliferation, migration, and differentiation of neuronal precursors, resulting in increased neurogenesis in the injured basal ganglia and cortex. 47,51,52 Although therapeutic hypothermia has improved the outlook of infants with HIE, 53,54 there remains a pressing need for neuroprotective therapies that will further reduce the high rate of neurologic disabilities.…”
Section: Sensitivity Analysesmentioning
confidence: 99%